Caracterização de uma população exposta à agrotóxicos em assentamento rural próximo à cidade de Cascavel-Pr - Demito Santos, Thalita Faleiros (2020)
The consumption of pesticides has been increasing in agricultural production in our country, and its excessive use has become a public health problem. Rural workers and their families constitute the most affected portion of society, as they are directly exposed to such products. This study has a qualitative and quantitative focus and proposes to make an analysis of individuals exposed to pesticides in a rural settlement near the city of Cascavel - PR, where they have lived for years. The present work aims to characterize the population through the application of chronic intoxication protocols already established according to the Health Department of the State of Paraná filed at the Toxicology Assistance Center of the city of Cascavel - PR. The protocols are made up of evaluation sheets composed by structured questionnaires with closed questions to evaluate the exposure time, the pesticides with which they had contact, the number of poisonings of each individual and their health consequences. The sample consisted of 138 people, where we found 57.97% of the population being female, 55.07% of the white race, 48.55% of the population are farmers, 52.90% have already entered in contact with pesticides, 37.68% have not completed elementary school and 82.61% of the population has a family income of up to two minimum wages. It must be taken into account that there is the possibility of environmental contamination caused by farms located near the rural settlement.